2006
DOI: 10.1074/jbc.m604748200
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Overexpression of Nrf2-dependent Heme Oxygenase-1 in A549 Cells Contributes to Resistance to Apoptosis Induced by Epigallocatechin 3-Gallate

Abstract: Epigallocatechin 3-gallate (EGCG), the major polyphenol found in green tea, exerts antiproliferative and proapoptotic effects in many cancer cells. However, we found that among many cancer cells human lung adenocarcinoma A549 cells are markedly resistant to apoptosis induction by EGCG (even at 100 M for 72 h). Heme oxygenase-1 (HO-1) induced by stress stimuli represents a prime cellular defense mechanism, but it may be associated with enhanced cell proliferation and chemoresistance in some cancer cells. Becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
160
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(174 citation statements)
references
References 56 publications
9
160
0
5
Order By: Relevance
“…In fact, formation of EGCG-thiol conjugates was detected only at high doses (400 mg/kg) following intraperitoneal injection in mice (Sang et al 2005). Meanwhile, high-dose EGCG reduced the expressions of antioxidant enzymes, including HO-1, SOD, and catalase (Kweon et al 2006;Kim et al 2010). Along a similar line, our present results revealed that 1% GTPs dramatically decreased the mRNA expressions of HO-1 and NQO1 in the kidneys and livers of nontreated mice (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…In fact, formation of EGCG-thiol conjugates was detected only at high doses (400 mg/kg) following intraperitoneal injection in mice (Sang et al 2005). Meanwhile, high-dose EGCG reduced the expressions of antioxidant enzymes, including HO-1, SOD, and catalase (Kweon et al 2006;Kim et al 2010). Along a similar line, our present results revealed that 1% GTPs dramatically decreased the mRNA expressions of HO-1 and NQO1 in the kidneys and livers of nontreated mice (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…The mechanisms of action of theanine against the migration and invasion of A549 cells require further investigation. It should be mentioned that theanine has displayed an anticancer activity comparable to EGCG in the suppression of some kinds of cancer cells such as A549 and hepatoma AH109A cells in vitro and/or in in vivo models (Kweon et al 2006;Zhang et al 2002). This is the first time to report that theanine significantly reduces cell viability of human nonsmall cell lung cancer and leukemia cells as well as cell migration and invasion of human lung cancer cells.…”
Section: Resultsmentioning
confidence: 86%
“…Many anti-cancer drugs induce apoptosis by producing reactive oxygen species (ROS) in cancer cells; therefore, its antioxidant and cytoprotective potential could be considered the 'dark side' of Nrf2 signaling as regards the therapeutic action of these drugs. This perspective is corroborated by reports demonstrating that up-regulation of Nrf2 downstream genes including heme oxygenase-1 (HO-1) and NAD(P)H:quinone oxidoreductase 1 (NQO1) is related to the resistance of cancer cells to chemotherapy (Kweon et al, 2006), and that down-regulation of Nrf2 causes radiosensitization (Singh et al, 2010). Therefore, Nrf2/ARE regulators are needed for a new therapeutic approach against cancer as adjuvant chemotherapeutic drugs.…”
Section: Introductionmentioning
confidence: 73%